STUDENTS’ PERCEPTION ON GOOGLE MEET VIDEO CONFERENCING PLATFORM DURING ENGLISH SPEAKING CLASS IN PANDEMIC ERA - Berita Mambarasi Nehe (University of Kuningan, 2021)
The aim of the research was to investigate students’ perception while teaching learning process in 16 meeting by having google meet video conferencing. Method of the research used qualitative research by focusing at descriptive analysis to explore students’ perception in English speaking class as it was followed by 13 English students at the second semester of English study program of STKIP Setia Budhi Rangkasbitung who join speaking lesson. Instruments used were observation, questionnaire, and interview. The results of the research about students’ perception emphasized on interaction, teaching learning process, psychological aspects, and speaking skills. The researcher found that interaction showed that there were three patterns of interaction, they were interaction lecturer-students, students-lecturer, and students-students interaction. The three interactions happened well since the number of them was 100% and all students were involved in speaking activity. Teaching learning process was done as usual like in a real classroom such as pre-activity, main activity, and post-activity. In the form of psychological aspects, students were happy, secure, confident, and brave. Data showed 100%, it meant that they did not have any barriers during English speaking class with google meet video conference. Speaking skills in the form of pronunciation, vocabulary, grammar, fluency, and comprehension. Students kept having their right to learn about those aspects supported by the teacher in google meet. When students did some mistakes, lecturer explained directly in general at the end of class and this way was very helpful for students in learning speaking. From these findings, the conclusion was the usage of google meet video conferencing in the speaking class showed positive respond that students’ perception on google meet showed mostly perceive the advantages rather than disadvantages of google meet video conferencing provided.